Bcl6 Preserves the Suppressive Function of Regulatory T Cells During Tumorigenesis - Li, Yiding; Wang, Zhiming; Lin, Huayu; Wang, Lisha; Chen, Xiangyu; Liu, Qiao; Zuo, Qianfei; Hu, Jianjun; Wang, Haoqiang; Guo, Junyi; Xie, Luoyingzi; Tang, Jianfang; et al. (Frontiers in Immunology, 2020)
During tumorigenesis, tumor infiltrating regulatory T (Treg) cells restrict the function of effector T cells in tumor microenvironment and thereby promoting tumor growth. The anti-tumor activity of effector T cells can be therapeutically unleashed, and is now being exploited for the treatment of various types of human cancers. However, the immune suppressive function of Treg cells remains a major hurdle to broader effectiveness of tumor immunotherapy. In this article, we reported that the deletion of Bcl6 specifically in Treg cells led to stunted tumor growth, which was caused by impaired Treg cell responses. Notably, Bcl6 is essential in maintaining the lineage stability of Treg cells in tumor microenvironment. Meanwhile, we found that the absence of follicular regulatory T (Tfr) cells, which is a result of Bcl6 deletion in Foxp3+ cells, was dispensable for tumor control. Importantly, the increased Bcl6 expression in Treg cells is associated with poor prognosis of human colorectal cancer and lymph node metastasis of skin melanoma. Furthermore, Bcl6 deletion in Treg cells exhibits synergistic effects with immune checkpoint blockade therapy. Collectively, these results indicate that Bcl6 actively participates in regulating Treg cell immune responses during tumorigenesis and can be exploited as a therapeutic target of anti-tumor immunity.